Activated carbons as catalytic support for Cu nanoparticles - Martin, F.J.; Yang, C.; García-Mateos, Francisco José; Guerrero-Pérez, María Olga; Rodríguez-Mirasol, José; Cordero-Alcántara, Tomás (My University, 2018)
There are a wide range of catalytic applications for Cu-based nanoparticles materials, since Cu is an abundant and inexpensive metal and Cu nanoparticles possess unusual electrical, thermal and optical properties. The possible modification of the chemical and physical properties of these nanoparticles using different synthetic strategies and conditions and/or via postsynthetic chemical treatments has been largely responsible for the rapid growth of interest in these nanomaterials and their applications in catalysis. A previous work have explored the possibilities of SBA-15 (1,2) as support for Cu nanoparticles. In the present contribution, those results will be compared with the use of a carbon material as support, since activated carbon present many advantages with respect SBA, as the high surface area.
Keywords: Carbón activado; Nanopartículas; Activated carbons; Cu; Nanoparticles; Catalytic supports